Macro- and microscopic changes in veins with short-term central venous catheters: an observational autopsy study - Rockholt, Mika M.; Naddi, Leila; Badri, Ahmed M.; Englund, Elisabet; Kander, Thomas (BMC anesthesiology, 2024)
Centrally inserted central catheters (CICCs) are indispensable in modern healthcare, but unfortunately, come with complications. Catheter-related thrombosis is a well-known complication reported to occur in 5-30% of patients with CICC. There is a paucity of studies that report the incidence of catheter-related thrombosis after the introduction of real-time ultrasound insertion guidance as clinical practice. This study aimed to demonstrate any pathological macro- or microscopic changes in the vein wall associated with CICCs. The study was approved by the Swedish Ethical Review Authority and was conducted at a large university hospital. The study included 12 patients with a short-term CICC who were subject to autopsies. Vessels with inserted catheters were macroscopically and microscopically examined. In total, seven female and five male patients with a median age of 70 (interquartile range 63-76) were included. With one exception, all patients received routine thromboprophylaxis throughout the period with CICC. Most inserted CICCs were 9.5 French (54%) and were inserted in the internal jugular vein (92%). The median time with CICC was seven days (interquartile range 1.8-20). At autopsy, thrombi were observed in all cases (100%), macroscopically and microscopically, attached to the distal portion of the CICC and/or the adjacent vessel wall. Inflammatory changes in the vessel walls were seen in all cases, and varying degrees of fibrosis were demonstrated in eight cases (67%). This autopsy study demonstrated that catheter-related thrombus formation with adjacent inflammatory and fibrotic vessel wall thickening was very common, despite a limited period of catheter use. The consequences of these findings are important, as thrombi may cause pulmonary embolism and possibly lead to catheter-related infections, and since inflammatory and fibrotic vessel wall thickening may evolve into chronic venous stenosis. Furthermore, the findings are a cause of concern, as CICCs are indispensable in modern healthcare and complications may be masked by the general disease that was the indication for CICC insertion.